EVALUASI MUTU BETON MENGGUNAKAN BETON INTI DIAMETER KECIL - Yulius Rakhman (Jurnal Keteknikan dan Sains (JUTEKS), 2019)
One of the causes of limited sampling on concrete structures is that there are reinforcement in the concrete structure, so that when using a large diameter drill core, can damage the concrete structure. Therefore a study of small diameter concrete was conducted to predict the compressive strength of cylindrical concrete. Test specimens in the form of concrete cylinders with dimension 10 cm x 20 cm, 2 concrete plates with dimension 45cm x 45cm x 13cm and 4 concrete beams with dimensions 70 cm x 30 cm x 15 cm by taking concrete using a drill core diameter of 2" and 1". Two concrete slabs and two concrete beams with concrete strength (f'c) 20 MPa (MSA 20mm and 10mm) while two concrete concrete slabs and two concrete beams with concrete strength (f'c) 30 MPA (MSA 20mm and 10mm). Types of tests carried out include testing the compressive strength of concrete, core concrete normality test, modulus of elasticity and compressive strength of the core concrete. From test results, can be concluded that the compressive strength of core concrete with sample in the direction of casting for a diameter of 2 inches and concrete strength of 20 MPa (MSA 20 mm and 10 mm) meets the requirements and can be recommended with number samples of 25, whereas for diameter 1" the number of samples must be added.